Distribution of Trichoderma spp. in cumin rhizosphere and their potential in suppression of wilt - KUSUM MATHUR, R. K. VYAS* and (Indian Phytopathology, 2002)
In a sample survey of 15 conventional cumin fields of western Rajasthan the wilt caused by Fusarium oxysporum f. sp. cumini (Foe) was severe (20 - 35%) in five, moderate Â« 15%) in six, and absent in four fields. Wilt incidence was high in fields where pearl millet was the rainy season crop, and less in those with summer fallow or summer ploughing. In the fields where the disease was either absent or low, high population density of Trichoderma spp. and low of Fusarium spp including Foe were recorded. Trichoderma spp. effectively inhibited the growth and I or sporulation of Foe in vitro through production of volatile and non-volatile antibiotics. In a pot trial T. aureoviride and T. harzianum as seed plus soil application resulted in significantly higher germination and lower disease. High densities of Trichoderma spp, and considerably low of Foe (over the untreated controls) were recorded in cumin rhizosphere at 30, 60 and 90 days of sowing. Combination of both the SCAs was more effective than the individual for wilt suppression.